Determinan keputusan penggunaan pembayaran digital: Peran niat sebagai mediasi literasi keuangan - Muchamad Khozin Chanafaro; Sari, Linda Purnama (Journal of Business & Banking, 2024)
This study aims to examine the influence of financial literacy, risk perception, lifestyle, and the use of digital payments, all of which are mediated. by intention, on Generation Z in Surabaya. This study uses quantitative methods and purposive sampling techniques involving 175 Generation Z respondents in Surabaya. The data analysis technique uses a structural equation model with partial least squares (SEM-PLS). The results of the study indicate that financial literacy has a direct influence on the intention and use of digital payments, while risk perception does not directly affect the intention to use digital payments but directly affects the use of digital payments. Meanwhile, lifestyle does not directly affect the use of digital payments. This study proves that the intention to use digital payment applications is able to mediate the influence of financial literacy on the use of digital payments. Yet, the intention to use digital payment applications is not able to mediate the perception of risk in the use of digital payments. It can be implied that financial literacy is important for increasing the use of digital payment applications for Generation Z in Surabaya through high intentions.